Food intake pattern and nutritional status of hemodialytic patients (Asian Journal of Medical and Biological Research, 2021)
The incidence of renal disease is increasing at an alarming rate in Bangladesh. Malnutrition is directly correlated with the prevalence with these diseases. A total of 120 dialysis patients from both sexes having mean age 45±13. 79 years undergoing hemodialysis were enrolled for the study in Khulna city, Bangladesh. Information regarding disease history and associated co morbidities were collected from patient’s files. The personal information, prevalent vices, exercise behavior, dietary modifications and clinical and health status of the patients were recorded by using pre-tested questionnaire. Etiology of the chronic renal disease, complications and biochemical parameters were documented from the case files. Renal failure was more prevalent among male than in female. Diabetes mellitus (31.67%) were the most common etiology for chronic renal failure. Pallor of eyes was the most prevailing sign and the most common symptoms are breathlessness (98%), oliguria (88%), anorexia (67%) and nausea (60%). Nutritional status was assessed by anthropometric measurements using body mass index (BMI), mid arm circumference (MAC) and waist hip ratio (WHR). According to BMI, 43% male are grouped in normal category whereas majority of females (52%) are underweight with no overweight female respondents. 80% male had low adequacy of energy whereas all the female patients had adequacy of energy, carbohydrate and protein on low level. Dietary data was obtained by using 24-hour dietary recall and food frequency questionnaire. Actual intake of calories, protein, fats and minerals was lower than the recommended intake for hemodialysis patients. More than 50 percent of patient on hemodialysis were at risk of malnutrition. Around 32% respondents included fruits as per doctor’s advice whereas water and salted foods were restricted to three fourth of patients to protect kidney. Proper assessment of nutritional status, nutritional management and dietary modification can play a central role in preventing malnutrition of hemodialysis patients.Asian J. Med. Biol. Res. December 2020, 6(4): 746-753